Impact of physical therapy on functional capacity and life quality of patients with chronic kidney disease - Georgia Miranda Tomich; Luciana Souza Bernardino; Fabiana Oliveira Ferreira
Introduction Studies have demonstrated beneficial effects of exercise in patients with chronic kidney disease, however, based on current scientific literature, more research is needed to increase evidence level of potential effects of physical activity for this population. Objective To evaluate effects of physical therapy based on the supervised exercise practice on functional capacity and life quality of patients with chronic kidney disease. Material and methods This quasi-experimental study, with repeated measures design, was conducted in the ambulatory of physical therapy, in a public hospital, located in a city of the state of Pará (north region of Brazil). Functional capacity and life quality were assessed at baseline and after six weeks of aerobic and resistance training performed three times per week on alternate days with hemodialysis. Results Eight patients (3M / 5F) with a mean age of 60.38 years (SD = 14.75) were evaluated. There was significant increase of 24% in distance walked in six minute walk test (p = 0.007), and of 47% in number of repetitions during sit-to-stand test (p = 0.002); there was also significant improvement in emotional role (p = 0.043) of life quality assessed with SF36 questionnaire. Conclusion There was a positive impact of only six weeks of rehabilitation with physical exercise on functional capacity and emotional role of life quality of patients with chronic kidney disease.